KETERLEKATAN SOSIAL INOVASI PRODUK BANK SYARIAH DI INDONESIA - AM. M. Hafidz MS. (Jurnal Hukum Islam, 2015)
This study aims at analysing how Sharia Bank products innovation may be embedded with the social background where the products were aimed to be. There were four indication of why this case mattered: (1) the social construction of the rise of sharia bank, (2) sharia bank values in developing its products, (3) the role of Syaria Advisory Board in maintaining sharia compliance, and (4) the dominance of micro-finance. How the social background and values which surround sharia bank are embedded in its product innovation shows that sharia bank is not only an an sich business entity but more than that, it's an integrated part of kaffah/principled Islamic values.